Artists' Voices in Cultural Policy Careers, Myths and the Creative Profession after German Unification - Wesner, Simone (New Directions in Cultural Policy Research, 2018)
This volume examines visual artists' careers in the East German region of Saxony, as seen through the lens of cultural policy studies. The book discusses how myth binaries, memory layers and identity markers shaped artists professional lives in an interwoven and fluid approach following German unification, taking a fresh look at the intricacies of visual artists' careers within the specifics of the cultural, social and political changes. It surveys artists' professional practice and work under the new framework of the professional class, and discusses the implications for the profession of artists with special reference to visual artists. Simone Wesner looks beyond geographical and political contexts and provides the reader with a longitudinal narrative that produces a revised understanding of artists' careers within the cultural policy context. .